(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Migraine is a type of Headache characterized by moderate to severe throbbing pain, generally associated with nausea, vomiting and light sensitivity. It can be correlated to Ardhavbhedaka, which according to the Ayurvedic science is caused by simultaneous vitiation of all the three Doshas viz. Vata, Pitta and Kapha. Motion sickness is also a common disorder wherein patient suffers from symptoms like nausea, vomiting, increased salivation, dizziness, upon getting triggered by certain movements. In this case study, a female patient of middle age group (Madhyam Avastha) suffering from long standing migraine and motion sickness since past 15 years (on and off), hampering her day to day activities, was administered with the treatment protocol as per Ayurveda resulting in significant relief to her symptoms. The treatment, planned according to her pulse diagnosis and clinical examination, was based on herbal supplements, Panchakarma (detoxification) in the form of Virechana, home remedies, Marmaa therapy, dietary and lifestyle modifications. The treatment was focused on removing the toxins (Aam) from the body with the help of detox (Virechana). This also resulted in alleviation of the vitiated Vata and Pitta Doshas and restoration of the Jatharagni (digestive fire). The treatment modality has been effective to reduce the episodes significantly.